2020
DOI: 10.1016/j.molstruc.2020.128080
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectrum and intramolecular hydrogen bonding in 1,2-butanedithiol

Abstract: The jet-cooled rotational spectrum of 1,2-butanedithiol was observed in the frequency region 2-8 GHz. Two conformers were detected for the molecule, corresponding to trans-and gauchecarbon molecular skeletons, both sharing a gauche arrangement of the two thiol groups. The structural analysis included a ground-state effective structure, isotopic substitution coordinates, B3LYP-D3(BJ) density functional molecular orbital calculations and non-covalent interactions mapping with NCIPlot. The structural data confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Thiol-alcohol gas-phase hydrogen bonds were also reported for the monohydrates of furfuryl 36 and thenyl 37 mercaptan ( r (S–H···O) = 2.22–2.44 Å; r (O–H···S) = 2.43–2.58 Å), but the experimental investigations of gas-phase hydrogen bonds between thiols are still scarce. 34 , 35 Protein crystal contacts between the cysteine thiol and the sulfur atom in methionine or cysteine have shorter average values of r (S–H···S) = 2.55(47) Å. 49 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thiol-alcohol gas-phase hydrogen bonds were also reported for the monohydrates of furfuryl 36 and thenyl 37 mercaptan ( r (S–H···O) = 2.22–2.44 Å; r (O–H···S) = 2.43–2.58 Å), but the experimental investigations of gas-phase hydrogen bonds between thiols are still scarce. 34 , 35 Protein crystal contacts between the cysteine thiol and the sulfur atom in methionine or cysteine have shorter average values of r (S–H···S) = 2.55(47) Å. 49 …”
mentioning
confidence: 99%
“… Here, we explore the replacement of oxygen in phenol by a heavier less-electronegative chalcogen atom like sulfur, proving that it maintains S–H···S hydrogen bonding while simultaneously resulting in a π-stacking homodimer. The work is extended also to the thiophenol trimer, complementing our view on sulfur hydrogen bonding and allowing comparisons with the phenol and aniline trimers.…”
mentioning
confidence: 99%
“…Armed with such an arsenal of techniques, our group carried out several gas-phase studies on model complexes , and demonstrated, by considering the red shifts in vibrational frequencies of X–H oscillators, binding energies, geometrical parameters, and magnitude of donor–acceptor orbital overlap, that O–H···S and N–H···S/Se H-bonds have strengths comparable to those of conventional H-bonds. It was also concluded that those S/SeCHBs are a combination of electrostatic, charge-transfer, and dispersion forces. , The fascinating role of C–H···S/Se H-bonds in several biochemical systems, as well as in crystal structures, was noted. These H-bonds were earlier considered to be similar to van der Waals interactions .…”
Section: Hydrogen Bonds With Sulfur and Selenium: Changing Perceptionsmentioning
confidence: 97%
“…High-resolution rotationally-resolved 9,10 studies are still scarce, as illustrated by the hydrogen sulphide dimer, reported only in 2018. 11 To date, rotational spectroscopy has addressed several intra- 12,13,14 and intermolecular interactions in hydrogen sulfide dimers or sulfur-containing complexes, like O-H•••S, 15 18 and S-H•••. 19,20,21 The gas-phase information can thus complement previous molecular descriptions relying solely on crystal data 3 and theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%